The Transition to Adulthood of Contemporary Delinquent Adolescents - Kang, Timothy (Journal of developmental and life-course criminology, 2019)
Purpose: To document how age-graded social bonds, specifically employment and partnering, are timed and sequenced during the transition to adulthood among contemporary delinquent adolescents, and how these trajectories compare with those of non-delinquents to better inform contemporary desistance research. Methods: Multiple sequence and cluster analyses were conducted using data from the National Longitudinal Survey of Youth 1997 (n = 8984) to describe the trajectories young adults take through the transition to adulthood. Multinomial logistic regression was used to predict cluster membership by adolescent criminal behavior and arrest history. Results: Contemporary delinquent adolescents are significantly less likely to experience traditional sources of informal control (e.g., marriage, full-time employment) compared with their non-delinquent counterparts and past cohorts, and those who do experience similar age-graded controls tend to do so later during the transition to adulthood. Crime and arrests during adolescence are also more consequential in determining partnering and employment trajectories for women compared with men. Conclusions: In comparison with past cohorts, contemporary delinquent adolescents are far less likely to experience the traditional social bonds that have been theorized to encourage desistance from crime as they transition to adulthood, and combine partnering and employment roles in a variety of trajectories. Future research in life course criminology searching for social determinants of long-term desistance and persistence in crime need to consider the new schedule of age-graded social bonds experienced by contemporary delinquent adolescents.